CO2-driven surface changes in the Hapi region on Comet 67P/Churyumov–Gerasimenko. Issue 4 (11th September 2022) - Davidsson, Björn J R; Schloerb, F Peter; Fornasier, Sonia; Oklay, Nilda; Gutiérrez, Pedro J; Buratti, Bonnie J; Chmielewski, Artur B; Gulkis, Samuel; Hofstadter, Mark D; Keller, H Uwe; Sierks, Holger; Güttler, Carsten; et al.
ABSTRACT: Between 2014 December 31 and 2015 March 17, the OSIRIS cameras on Rosetta documented the growth of a 140 -m wide and 0.5 -m deep depression in the Hapi region on Comet 67P/Churyumov–Gerasimenko. This shallow pit is one of several that later formed elsewhere on the comet, all in smooth terrain that primarily is the result of airfall of coma particles. We have compiled observations of this region in Hapi by the microwave instrument MIRO on Rosetta, acquired during October and November 2014. We use thermophysical and radiative transfer models in order to reproduce the MIRO observations. This allows us to place constraints on the thermal inertia, diffusivity, chemical composition, stratification, extinction coefficients, and scattering properties of the surface material, and how they evolved during the months prior to pit formation. The results are placed in context through long-term comet nucleus evolution modelling. We propose that (1) MIRO observes signatures that are consistent with a solid-state greenhouse effect in airfall material; (2) CO2 ice is sufficiently close to the surface to have a measurable effect on MIRO antenna temperatures, and likely is responsible for the pit formation in Hapi observed by OSIRIS; (3) the pressure at the CO2 sublimation front is sufficiently strong to expel dust and water ice outwards, and to compress comet material inwards, thereby causing the near-surface compaction observed by CONSERT, SESAME, and groundbased radar, manifested as the 'consolidated terrain' texture observed by OSIRIS.